ENHANCING THE GRAMMAR PROFICIENCY OF INDONESIAN MIGRANT WORKERS IN MALAYSIA - Ahmadi, Ahmadi; Sholakhuddin, Faris (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IAIN Ponorogo, 2023)
In this community service, the problem at the English Academy Bengkulu Malaysia (EABM) was the low quality of grammar among Indonesian migrant workers. In addition, an asset developed to address the above problem was the individual asset in the form of instructors because instructors have a crucial role in improving the quality of grammar learning. This community service aimed to enhance the quality of grammar among Indonesian migrant workers by improving instructor competence. The method used in this community service was ABCD (Asset-Based Community-Driven Development) employing two stages, namely: first, asset mapping using community mapping, and second, asset selection using low hanging fruit scale. The results of this community service were: (1) the preparation stage which includes problem discovery, asset mapping, asset determination, and determination of community service programs. (2) the implementation stage which includes strengthening active learning methodologies for instructors and using songs as a learning medium. (3) the monitoring stage to assess the success of the program, with success indicated by improved grammar competence of participants during speaking sessions in the learning material preview.